Analisis Potensi Kebangkrutan PT. Berlian Laju Tanker, Tbk. dengan Menggunakan Altmanâs Z Score - Iswandi, Iswandi (Binus Business Review, 2012)
PT. Berlian Laju Tanker, Tbk. (BLTA) is a company engaged in the ocean transportation services listed on the Indonesia Stock Exchange and the Singapore Stock Exchange. In 2009 and 2010 BLTA experienced a net loss. At the end of 2011 the company rocked the financial markets in Indonesia and Singapore being unable to meet financial obligations to financial institutions and corporate bondholders. Given such conditions until the end of August 2012 BLTA can not submit audited financial statement of year 2011 to the authorities of stock exchange and public. By using the 2007 to 2010 audited financial statements and June 2011 inhouse financial statement were analyzed using Altmans Z score model can be known that since 2007 BLTA produce a Z score were classified bankruptcy. Investors should analyze the financial condition by using Z Score in order to minimized shareholders and bondholders potential losses.